Bridging Computer Programming Education with Quantum Computing and Art: Temporal Rhythms Observed in Space - Michael ROROS; James BRAMAN; Cody MAYFIELD; Mel AKHIMIEMONA (Communications of International Proceedings, 2025)
This paper introduces Temporal Rhythms Observed in Space (Trois), an educational art-based framework designed to teach computer programming concepts through an interactive generative system inspired by quantum computing concepts. Traditional programming courses rarely expose students to emerging topics like quantum computing; instead, they focus on traditional programming concepts. Trois addresses this gap by combining cellular automata with visual patterns inspired by quantum time crystals to create an accessible, creative learning experience. While not a complete simulation of a quantum system, Trois conceptually models behaviors such as temporal symmetry breaking, emergent oscillations, and many-body interactions. The aim is to provide students, especially those without advanced mathematical training, with a hands-on framework to explore programming constructs alongside quantum-inspired thinking. The framework is implemented in Python, using a modified version of Conway's Game of Life, extended with real-time visual feedback and interactive parameters. Students can experiment with rule variations, observe evolving states, and manipulate inputs to better understand core programming ideas such as loops, conditionals, and state transitions. Future work includes broader deployment in programming curricula and additional features to further align with quantum computing concepts. This paper discusses Trois' major components, current implementation details, and the next steps for using it for a programming course.
Keywords: Programming Education; Generative Art; Quantum-Inspired Computing